Державне регулювання іпотечного кредитування аграрної сфери в Україні та країнах Євросоюзу - Трусова, Наталя Вікторівна; Трусова, Наталья Викторовна; Trusova, Natalia; Гривківська, С. М. (My University, 2019)
UK: У статті розглянуто державне регулювання іпотечного кредитування аграрної сфери в Україні та країн ЄС. Встановлено, що іпотечне кредитування під заставу земель сільськогосподарського призначення має відбуватись на пільгових умовах з урахуванням специфіки виробництва сільськогосподарських підприємств, цілей кредиту та місцезнаходження заставної земельної ділянки. Пільгове кредитування має здійснюватися шляхом часткової компенсації відсоткової ставки за іпотечним кредитом за рахунок бюджетних коштів або прямих компенсаційних виплат (дотацій) банківським установам (кредиторам). Іпотечні кредити під об’єкти нерухомості сільськогосподарського виробництва підприємств-позичальників мають надаватись спеціалізованими іпотечними банками. На основі досвіду краї Євросоюзу запропоновано шляхи розвитку іпотечного кредитування сільськогосподарських підприємств в Україні. RU: В статье рассмотрены государственное регулирование ипотечного кредитования аграрной сферы в Украине и стран ЕС. Установлено, что ипотечное кредитование под залог земель сельскохозяйственного назначения должно проводиться на льготных условиях с учетом специфики производства сельскохозяйственных предприятий, целей кредита и местонахождения залоговых земельных участков. Льготное кредитование должно осуществляться путем частичной компенсации процентной ставки по ипотечному кредиту за счет бюджетных средств или прямых компенсационных выплат (дотаций) банковским учреждениям (кредиторам). Ипотечные кредиты под объекты недвижимости сельскохозяйственного производства предприятийзаемщиков должны предоставляться специализированными ипотечными банками. На основе опыта стран Евросоюза предложены пути развития ипотечного кредитования сельскохозяйственных предприятий в Украине. EN: The subject of research is mortgage relations, in which land plots of agricultural purpose are the collateral for the loan. The aim of the study is to develop theoretical ambushes, scientific and practical recommendations for state regulation of the mortgage lending in agriculture of Ukraine with consideration of foreign experience. The study used the following research methods: abstract-logical (theoretical generalizations and forming conclusions); graphic (for a good image of economic processes and numerical values, and their ratios). It is established that in the vast majority of EU land-mortgage lending occurs in a single-level and two-level model, according to which credits against the pledge of agricultural lands occurs in a opened system of mortgage lending by specialized credit institutions (mortgage banks). Resources for lending of funds accumulated from bonds with fixed interest income that the Bank issues under the provision of the land plots. The interest rate on the loan is fixed from the market value of the land, and the amount of the loan granted is limited by the percentage of its value. The most important component of the regulation of land mortgage relations in agriculture of the EU countries the state is the concessional lending, namely bonificacion % – partial compensation of interest rate on the loan at the expense of budgetary funds. For the development of land mortgage lending in Ukraine it is necessary: to recognize the land capital; to create the infrastructure of the State land mortgage Bank; to provide loans secured agricultural land at a concessional rate of 3-4 %, for a period of not less than 25-30 years, with the possibility of deferred payment, and for the first 1-2 years to provide vacation credit; to reduce lending rates to use bonificacion; mortgage loans should be granted only to agricultural producers. The suggestions contained in the article have practical value and can be used to develop an effective system of land mortgage lending in agriculture of Ukraine.
Государственное регулирование ипотечного кредитования аграрной сферы в Украине и странах Евросоюза
State regulation of the mortgage lending of agriculture in Ukraine and European Union countries
Keywords: іпотечне кредитування; застава; земельна ділянка; сільське господарство; відсоткова ставка; державне регулювання; ипотечное кредитование; залоговый земельный участок; сельское хозяйство; процентная ставка; государственное регулирование; mortgage lending; pledge; land plot; agriculture; interest rate; state regulation